Recall the beta function definition and gamma identity,
![\displaystyle \mathrm{B}(x,y) = \int_0^1 t^(x-1) (1-t)^(y-1) \, dt = (\Gamma(x) \Gamma(y))/(\Gamma(x+y))](https://img.qammunity.org/2023/formulas/mathematics/college/hb3bjyrfb6gfm1yo0myrq1l5rycp5axat1.png)
Consider the sum
![\displaystyle S(x) = \sum_(m=1)^\infty (\Gamma(m) \Gamma(x))/(\Gamma(m+x))](https://img.qammunity.org/2023/formulas/mathematics/college/yxyiquevu4sn88fqiygpmb428hmc611uvl.png)
Compute it by converting the gammas to the beta integral, interchanging summation with integration, and using the sum of a geometric series.
![\displaystyle S(x) = \sum_(m=1)^\infty \mathrm{B}(m,x) \\\\ ~~~~ = \sum_(m=1)^\infty \int_0^1 t^(m-1) (1-t)^(x-1) \, dt \\\\ \int_0^1 (1-t)^(x-1) \sum_(m=1)^\infty t^(m-1) \, dt \\\\ ~~~~ = \int_0^1 (1-t)^(x-2) \, dt \\\\ ~~~~ = \int_0^1 t^(x-2) \, dt \\\\ ~~~~ = \frac1{x-1} = ((x-2)!)/((x-1)!) = (\Gamma(x-1))/(\Gamma(x))](https://img.qammunity.org/2023/formulas/mathematics/college/t9xgvwg159sxhd5lcfj5kkjuqxuf4g8ogg.png)
It follows that
![\displaystyle S(n+x) = \sum_(m=1)^\infty (\Gamma(m) \Gamma(n+x))/(\Gamma(m+n+x)) = (\Gamma(n+x-1))/(\Gamma(n+x))](https://img.qammunity.org/2023/formulas/mathematics/college/gt4v1sawkx2mo19gsdzi94frskuxsyrrjn.png)
Now we compute the sum of interest. It's just a matter of introducing appropriate gamma factors to condense the double series into a single hypergeometric one.
Recall the definition of the generalized hypergeometric function,
![\displaystyle {}_pF_q \left(\left.\begin{array}{c} a_1,a_2,\ldots,a_p\\b_1,b_2,\ldots,b_q\end{array}\right\vert z\right) = \sum_(n=0)^\infty ((a_1)_n (a_2)_n \cdots (a_p)_n)/((b_1)_n (b_2)_2 \cdots (b_q)_n) (z^n)/(n!)](https://img.qammunity.org/2023/formulas/mathematics/college/re3y3ettp3bsn6r4ipzes9d71rmecwbo55.png)
where
denotes the Pochhammer symbol, defined by
![\begin{cases}(0)_n = 1 \\ (a)_n = a(a+1)(a+2)\cdots(a+n-1) = (\Gamma(a+n))/(\Gamma(a))\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/7owqs1sn07n5s2ztm7h91zkotpqr84svvj.png)
We'll be needing the following identities later.
![(1)_n = n! = (\Gamma(n+1))/(\Gamma(1))](https://img.qammunity.org/2023/formulas/mathematics/college/zxrualodirtnee1zaxqo393xsq7bbvph7a.png)
![(x)_n = (\Gamma(n+x))/(\Gamma(x))](https://img.qammunity.org/2023/formulas/mathematics/college/un4q3xwgph5wv1cjqele02fo0jd35rcf37.png)
![(x+1)_n = (\Gamma(n+x+1))/(\Gamma(x+1))](https://img.qammunity.org/2023/formulas/mathematics/college/qa49cmk5mk39jl6ykw0uvsk66wugzd9qyw.png)
The
-sum is
![\displaystyle \sum_(m=1)^\infty (\Gamma(m))/(\Gamma(n+m+x)) = \frac1{\Gamma(n+x)} \sum_(m=1)^\infty (\Gamma(m)\Gamma(n+x))/(\Gamma(n+m+x)) \\\\ ~~~~~~~~ = (S(n+x))/(\Gamma(n+x)) \\\\ ~~~~~~~~ = (\Gamma(n+x-1))/(\Gamma(n+x)^2)](https://img.qammunity.org/2023/formulas/mathematics/college/h2r5qsacs0h3j9tl0d4m2h8lz3kbf8w19e.png)
Then the double sum reduces to
![\displaystyle \sum_(n=1)^\infty \sum_(m=1)^\infty (\Gamma(n)\Gamma(m)\Gamma(x))/(\Gamma(n+m+x)) = \sum_(n=1)^\infty (\Gamma(n)\Gamma(x)\Gamma(n+x-1))/(\Gamma(n+x)^2)](https://img.qammunity.org/2023/formulas/mathematics/college/di53mkau9gk364tkgy80uksww6hqio8fgq.png)
Rewrite the summand. We use the property
to convert to Pochhammer symbols.
![\displaystyle (\Gamma(n)\Gamma(x)\Gamma(n+x-1))/(\Gamma(n+x)^2) = (\Gamma(n)\Gamma(x)^2\Gamma(n+x-1))/(\Gamma(n+x)^2 \Gamma(x))](https://img.qammunity.org/2023/formulas/mathematics/college/l11zlxwzod7zolxl1gmn6aa5rg1fv9k4fr.png)
![\displaystyle . ~~~~~~~~ = \frac1{x^2} (\Gamma(n)\Gamma(x+1)^2\Gamma(n+x-1))/(\Gamma(n+x)^2\Gamma(x))](https://img.qammunity.org/2023/formulas/mathematics/college/rzemt3gwoc2556a684m6fs5225k5ep6rpk.png)
![\displaystyle . ~~~~~~~~ = \frac1{x^2} (\Gamma(n) (\Gamma(n+x))/(\Gamma(x)))/((\Gamma(n+x-1)^2)/(\Gamma(x+1)^2))](https://img.qammunity.org/2023/formulas/mathematics/college/te5ef983859p71t07mstw5oxi5emokvx0q.png)
![\displaystyle . ~~~~~~~~ = \frac1{x^2} ((n-1)! (x)_(n-1))/(\left[(1+x)_(n-1)\right]^2)](https://img.qammunity.org/2023/formulas/mathematics/college/acfr6vdkjbfozwtn0gkwjwcf1l5dutvf4h.png)
Now in the sum, shift the index to start at 0, and introduce an additional factor of
to get the hypergeometric form.
![\displaystyle \sum_(n=1)^\infty \frac1{x^2} ((n-1)! (x)_(n-1))/(\left[(1+x)_(n-1)\right]^2) = \frac1{x^2} \sum_(n=0)^\infty ((n!)^2 (x)_n)/(\left[(1+x)_n\right]^2) \frac1{n!} \\\\ ~~~~~~~~ = \frac1{x^2} \sum_(n=0)^\infty ([(1)_n]^2 (x)_n)/(\left[(1+x)_n\right]^2) \frac1{n!} \\\\ ~~~~~~~~ = \boxed{\frac1{x^2} \, {}_3F_2\left(\left.\begin{array}{c}1,1,x\\1+x,1+x\end{array}\right\vert1\right)}](https://img.qammunity.org/2023/formulas/mathematics/college/sbmkf8mjwcu582mojvdk0poj47vuvkhkdu.png)